2006
DOI: 10.1007/s00192-006-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and remission of urinary incontinence after hysterectomy—a 3-year follow-up study

Abstract: The aim of the study is to investigate the changes in continence status in a population of women hysterectomized in 1998-2000. Four hundred fifteen hysterectomized women who participated in a questionnaire study on continence status in September 2001 were retested with the same questionnaire on actual continence status in January 2005. As controls we used 97 women who had a laparoscopic cholecystectomy in 1999-2000 and were tested and retested similarly. Urinary incontinence was defined as involuntary urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…It seems likely that the duration of follow‐up plays an important role in the evaluation of outcomes 23,24 . Studies with a short follow‐up have not been able to demonstrate an increase in urinary incontinence after hysterectomy, 5,6,22 whereas results from studies with a longer follow‐up 7–9 are in line with our results showing increases in voiding difficulty, SUI, and use of medication for UI after hysterectomy. Thakar et al.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It seems likely that the duration of follow‐up plays an important role in the evaluation of outcomes 23,24 . Studies with a short follow‐up have not been able to demonstrate an increase in urinary incontinence after hysterectomy, 5,6,22 whereas results from studies with a longer follow‐up 7–9 are in line with our results showing increases in voiding difficulty, SUI, and use of medication for UI after hysterectomy. Thakar et al.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, a recent randomised study concluded that neither total nor subtotal hysterectomy adversely affected pelvic organ function at 12 months 6 . Similarly, three other prospective studies did not find an increased risk of UI after hysterectomy 5,21,22 . It seems likely that the duration of follow‐up plays an important role in the evaluation of outcomes 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…De-novo symptoms of all types of incontinence were noted in all groups with no differences between them, indicating that factors other than hysterectomy should be considered. Another well crafted study studying women over a 3-year period [31] has reported similar findings, with as many reporting improvement in incontinence symptoms as those showing deterioration.…”
Section: Pathophysiology and Risk Factorssupporting
confidence: 54%
“…Another explanation may be that follow up was too short to observe a significant difference. Other previous studies with a short follow up were also not able to demonstrate an increase in urinary symptoms after hysterectomy, 25–28 whereas studies with long‐term follow up did find increased urinary incontinence and voiding difficulties 6,29–31 …”
Section: Discussionmentioning
confidence: 93%